Get closer to activate It! : an educational tool for people with multiple disabilities - Bojanovic, Filip; Manresa Yee, Cristina; Abásolo Guerrero, María José; Larrea, Martín; Sanz, Cecilia Verónica (2015)
This paper presents an interactive system which offers multimodal feedback to users with severe to profound disabilities to improve their relationship with the environment allowing them to control it. The system is based on the information provided by a distance sensor connected to an Arduino board. The distance information is based on the position of the user’s hand, and it is then passed to six different action/reaction applications which offer motivation and engage users to train intentional motor movements of their upper body limbs and to improve their relationship with the environment.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Congreso Argentino de Ciencias de la Computación (21ro : 2015 : Junín, Argentina)
Keywords: ARDUINO; SISTEMAS USUARIO-MÁQUINA